Los estilos parentales y su influencia en el abuso o dependencia de alcohol en las estudiantes de la Carrera de Psicología Infantil y Educación Parvularia de la Universidad Nacional de Loja, periodo 2015-2016. - Ayora Loaiza, Cintya Alexandra (2016)
The research was focused on the theme: PARENTAL STYLES AND THEIR INFLUENCE ON ALCOHOL ABUSE OR DEPENDENCE ON childhood PSYCHOLOGY AND Early Childhood EDUCATION STUDENTS at Universidad Nacional de Loja, academic period 2015-2016. Whose main objective was to determine the relationship between parental styles and abuse or alcohol dependence on the major´s students. This research responded to a social scientist of a transversal study with a quantitative and a qualitative approach, which 118 students and 6 teachers were selected through a stratified random sampling. A survey was taken into account in order to identify the sociodemographic variables, a scale of Parenting Styles and Parental Inconsistency Perceived and the identification Questionnaire of Alcohol Use of Disorders, for which it was careful that these instruments respond to technical criteria. Among the results is highlighted that a 68% of students come from households with authoritarian parenting styles influence and the 10% of investigated overprotective styles have a high incidence to be drinkers risk and likely trigger alcohol dependence, respectively. So a psychoeducational proposal arises to deal better parenting styles, strengthen family relationships, and prevent the abuse of alcohol dependence. Key words. Parenting styles , abuse or dependence , alcohol, Scale Parenting Styles Questionnaire identification Alcohol Use Disorders , psychoeducational proposal.